En bostadsrättsförenings utmaningar och behov vid energieffektivisering : En kvantitativ studie om bygg- och installationstekniska lösningar - Olsson, Petter (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2025)
This thesis investigates energy efficiency improvements in a housing cooperative (BRF) in northern Sweden, with a particular focus on multifamily residential buildings from the Million Program era. These buildings face significant renovation needs due to outdated construction techniques and high levels of energy usage. In many cases, the technical lifespan of Million Program buildings has already been exceeded, necessitating extensive energy renovations to meet current energy standards. The aim of this work is to enhance knowledge about building and installation related energy efficiency measures that address the specific challenges and needs of a BRF. The study uses a combination of quantitative energy simulations and life cycle cost analysis (LCC) to evaluate the suitability of various energy efficiency measures considering a BRF's challenges and requirements. The quantitative analysis is conducted using the energy modeling software BIM Energy, examining parameters such as insulation of external walls and roofs, the installation of mechanical ventilation with heat recovery (MVHR) systems, and adjustments of heating systems. LCC, including sensitivity analysis, provides an economic dimension to the evaluation by highlighting investment costs, maintenance expenses, and potential energy savings over an extended period critical for BRFs with limited financial capacity. The sensitivity analysis explores how changes in discount rates and energy price trends impact the long-term cost implications of the proposed measures. The results indicate that measures such as improved insulation of the building envelope, particularly external walls, and the installation of MVHR systems are effective in reducing energy performance. However, these measures result in significant investment costs. The study also emphasizes that less extensive measures, such as adding roof insulation and optimizing adjustments of heating system achieve substantial energy savings at relatively low costs and can be implemented with minimal disruption ...